PD-1/PD-L1 inhibitors as a hope for smokers of non-small cell lung cancer patient - Yu, Zhuo; Zhang, Peiqing; Gu, Weikuan; Jiang, Xicheng (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
We read with great interest the recent review article by Warren (1) on the adverse health effects and costs associated with smoking after a cancer diagnosis. We noticed Dr. Warren concluded that priority should be placed on interventions that reduce the effect of medication and associated costs caused by continued smoking after a cancer diagnosis. Dr. Warren also pointed out that research is desperately needed to ascertain if the adverse effects of smoking can be overcome with an existing or forthcoming cancer treatment. We wondered whether Dr. Warren noticed the recently reported clinical trials on the effects of drugs of programmed death-1 (PD-1) and programmed death-ligand 1 (PD-L1) inhibitors on non-small cell lung cancer (NSCLC), and whether Dr. Warrant could comment on the potential benefit of PD-1 and PD-L1 drugs to NSCLC patients who are still smoking.